2009
DOI: 10.2337/db09-1091
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Gene Mutations Resulting in Early-Onset Diabetes: Marked Differences in Clinical Presentation, Metabolic Status, and Pathogenic Effect Through Endoplasmic Reticulum Retention

Abstract: OBJECTIVEHeterozygous mutations in the human preproinsulin (INS) gene are a cause of nonsyndromic neonatal or early-infancy diabetes. Here, we sought to identify INS mutations associated with maturity-onset diabetes of the young (MODY) or nonautoimmune diabetes in mid-adult life, and to explore the molecular mechanisms involved.RESEARCH DESIGN AND METHODSThe INS gene was sequenced in 16 French probands with unexplained MODY, 95 patients with nonautoimmune early-onset diabetes (diagnosed at <35 years) and 292 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
110
1
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(116 citation statements)
references
References 33 publications
1
110
1
4
Order By: Relevance
“…Using GFP-tagged preproinsulin constructs, a recent study reported no defect of R6C/R6H in the targeting of preproinsulin to insulin granules but suggested that ER stress might contribute to ␤ cell death and diabetes in patients carrying these mutations (14). Importantly, fusion with GFP (238 amino acids) triples the length of preproinsulin (110 amino acids) that may alter (increase) translocation efficiency (32)(33)(34).…”
Section: The Positive Charge In the N Region And Charge Gradient Flanmentioning
confidence: 99%
See 2 more Smart Citations
“…Using GFP-tagged preproinsulin constructs, a recent study reported no defect of R6C/R6H in the targeting of preproinsulin to insulin granules but suggested that ER stress might contribute to ␤ cell death and diabetes in patients carrying these mutations (14). Importantly, fusion with GFP (238 amino acids) triples the length of preproinsulin (110 amino acids) that may alter (increase) translocation efficiency (32)(33)(34).…”
Section: The Positive Charge In the N Region And Charge Gradient Flanmentioning
confidence: 99%
“…Recently, two preproinsulin SP mutants, preproinsulin R6C and R6H (here simply called R6C or R6H) have been linked to autosomal dominant late-onset diabetes in humans (14 -16). The molecular mechanism by which these mutants bring about diabetes has been speculated to involve ER stress (14), but the actual defect has remained unknown.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1) in which diabetes at adult age appeared to segregate as a dominant trait, while neonatal diabetes occurred in a recessive way. Screening for INS mutation in these two cases resulted in a lack of the PCR product of the coding exon 2 and the noncoding exon 1, while exon 3 and the neighboring tyrosine hydroxylase gene (TH) were well amplified (11). Thus, sequencing with several primer sets within the region between INS and TH was performed to characterize size and exact location of the deletion.…”
Section: Identification Of Insulin Gene Deletion In the Familymentioning
confidence: 99%
“…Recent studies indicated that autosomal dominant insulin gene mutations can cause permanent neonatal diabetes (PND) but also autoantibody-negative diabetes that is classified then as type 1B or maturity-onset diabetes of the young (MODY)-type diabetes (8)(9)(10). The molecular mechanism behind these cases with a MODY-like presentation was suggested to be defective trafficking of proinsulin and increased endoplasmic reticulum (ER) stress (11). Recessive mutations of the preproinsulin (INS) gene have also been identified as a novel cause of neonatal diabetes and were the commonest cause of isolated PND in the offspring of consanguineous parents (12).…”
Section: Introductionmentioning
confidence: 99%